Hubungan Pengetahuan dengan Kesiapan Wanita Menghadapi Menopause di Kecamatan Ciledug - Adin Syaefudin; Fadhila Arienda Humaira; Ahmad Nur Taufiqurrahman (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Based on data obtained in Indonesia in 2020, the number of women living in menopause was 30.3 million. In Banten Province, the menopausal age group (40-58 years) comprised 709,476 individuals, with 163,589 in Tangerang City, 20,221 in Ciledug District, and 2,704 in Parung Serab Village. This study used a quantitative research design with a cross-sectional approach. Primary data were collected, and the sample consisted of 30 respondents. The research instrument was a questionnaire. Univariate data were analyzed descriptively, while bivariate data were analyzed using the chi-square test. Univariate results showed that 17 respondents (56.7%) were prepared for menopause, while 13 (43.3%) were not. Bivariate analysis revealed a significant relationship between knowledge and women's readiness for menopause (P-value = 0.042 <